2014
DOI: 10.1002/elan.201300566
|View full text |Cite
|
Sign up to set email alerts
|

Cysteic Acid‐Modified Glassy Carbon Electrode for Monitoring Oxalic Acid (OA) Concentration During Its Electrochemical Oxidation at Ti/Pt Anode

Abstract: The aim of this manuscript is to develop a combined method for the detection and elimination of oxalic acid (OA) in aqueous environment. For that, the surface of glassy carbon (GC) electrode has been modified by oxidation of L‐cysteine using cyclic voltammetric (CV) technique. After modification, the formation of a compact and uniform cysteic acid layer film was achieved and it was confirmed by surface analysis (scanning electron microscopy (SEM) and atomic force microscopy (AFM)). Estimation of the linear ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…Meanwhile, the residuals of the regression by the DPV are displayed in Figure . As it can be observed, the results are randomly distributed around the zero, allowing a visual verification of the absence of a significant non linearity, in agreement with the statistical analysis approved (allowing a control of false positive and false negative errors (a=b=0.05)) by experts in the field . Additionally, the residuals of the regression by HPLC were plotted (Figure ), being very similar to the ones achieved by the electroanalytical analysis.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Meanwhile, the residuals of the regression by the DPV are displayed in Figure . As it can be observed, the results are randomly distributed around the zero, allowing a visual verification of the absence of a significant non linearity, in agreement with the statistical analysis approved (allowing a control of false positive and false negative errors (a=b=0.05)) by experts in the field . Additionally, the residuals of the regression by HPLC were plotted (Figure ), being very similar to the ones achieved by the electroanalytical analysis.…”
Section: Resultssupporting
confidence: 81%
“…As it can be observed, the results are randomly distributed around the zero, allowing a visual verification of the absence of a significant non linearity, in agreement with the statistical analysis approved (allowing a control of false positive and false negative errors (a = b = 0.05)) by experts in the field. [25,[41][42][43][44][45] Additionally, the residuals of the regression by HPLC were plotted (Figure 3), being very similar to the ones achieved by the electroanalytical analysis. This result clearly shows that, both approaches are comparable, robust and statistically reliable as well as this behavior clearly highlights the satisfactory ability of DPV to detect and quantify BQ with acceptable confidence, quantification precision and good sensitivity.…”
Section: Differential Pulse Voltammetrymentioning
confidence: 60%
See 1 more Smart Citation
“…16 Subsequently, Araújo et al reported a linear response between 1.5 -30 mM with a detection limit of 0.6 mM using the GCE modified cysteic acid layer film. 33 The long-term storage stability of the modified electrode toward OA sensing was studied over a week by monitoring its DPV responses to 5 mM OA in 0.1 M HClO4 with an intermittent usage (at 1 day intervals), and storage in air at room temperature when not in use. It was found that the response of the modified electrode gradually decreased to approximately 90% of its initial value within a week.…”
Section: Analytical Performance Of the Electrochemical Sensor For Oa mentioning
confidence: 99%
“…As nanopartículas apresentam propriedades diferentes daquelas exibidas pelo mesmo material quando estes se encontram em partículas de maior tamanho como bulks, e dentre suas principais características, o aumento da área superficial provocado pela modificação do eletrodo mostrou resultados promissores na detecção e quantificação do analito. 12,13 , platina 14,15 , ouro 16,17 , carbono vítreo [18][19][20][21][22] , entre outros; e materiais utilizados na modificação superficial, como óxidos metálicos 23,24 , polímeros condutores 25,26 e nanopartículas metálicas [27][28][29][30] .…”
Section: Introductionunclassified